MINERALOGY AND GEOCHEMISTRY OF REE IN GRANITIC PEGMATITES, BAIKAL REGION, EASTERN SIBERIA, RUSSIA - Shmakin B.M. (My University, 1992)
New INAA data for 35 bulk samples of metamorphic rocks, granites and pegmatites, together with some results of previous investigations of minerals containing REEs (allanite, betafite, euxenite, garnet and titanite) are discussed. Average concentrations of REEs in the pegmatites and granites are lower than the Clarke values for granite. The REE mineralization in the pegmatites may result from accumulation of these elements in the residual units, whereas the main parts of the pegmatitic bodies are free of REE.There are some regional differences between the Slyudyanka area (southwest end of Lake Baikal) and the Olkhon area (part of northwest Lake Baikal shore, close to Olkhon Island). Country rocks of the Slyudyanka area are richer in LREE, but in the Olkhon area they are enriched in HREE and Y. These differences are also evident in the composition of the chemically studied allanite, garnet and titanite from pegmatites of the two areas.Chondrite-normalized REE abundances in bulk samples of the pegmatites are more differentiated than those of the granites, and the REEs in granites are more differentiated than those in the metamorphic country rocks. Samples of the ultrametamorphic granites with distinct positive Eu anomalies have lower ΣREE contents relative to the gneisses. This fact suggests an essentially inert behaviour of Eu in the processes of granitization: such an anomaly is generated by the decreasing contents of all other lanthanides.